The Ca(2+)/Calmodulin/CaMKK2 Axis: Nature’s Metabolic CaMshaft - Marcelo, Kathrina L. (Trends Endocrinol Metab, 2016)
Calcium (Ca(2+)) is an essential ligand that binds its primary intracellular receptor Calmodulin (CaM) to trigger a variety of downstream processes and pathways. Central to the actions of Ca(2+)/CaM is the activation of a highly conserved Ca(2+)/CaM kinase (CaMK) cascade, which amplifies Ca(2+) signals through a series of subsequent phosphorylation events. Proper regulation of Ca(2+) flux is necessary for whole-body metabolism and disruption of Ca(2+) homeostasis has been linked to a variety of metabolic diseases. Herein, we provide a synthesis of recent advances that highlight the roles of the Ca(2+)/CaM kinase axis in key metabolic tissues. An appreciation of this information is critical in order to understand the mechanisms by which Ca(2+)/CaM-dependent signaling contributes to metabolic homeostasis and disease.